Development of multi-specific humanized llama antibodies blocking SARS-CoV-2/ACE2 interaction with high affinity and avidity - Jianbo Dong; Betty Huang; Zhejun Jia; Bo Wang; Sachith Gallolu Kankanamalage; Allison Titong; Yue Liu (Emerging Microbes and Infections, 2020)
ABSTRACTCoronaviruses cause severe human viral diseases including SARS, MERS and COVID-19. Most recently SARS-CoV-2 virus (causing COVID-19) has led to a pandemic with no successful therapeutics. The SARS-CoV-2 infection relies on trimeric spike (S) proteins to facilitate virus entry into host cells by binding to ACE2 receptor on host cell membranes. Therefore, blocking this interaction with antibodies are promising agents against SARS-CoV-2. Here we describe using humanized llama antibody VHHs against SARS-CoV-2 that would overcome the limitations associated with polyclonal and monoclonal combination therapies. From two llama VHH libraries, unique humanized VHHs that bind to S protein and block the S/ACE2 interaction were identified. Furthermore, pairwise combination of VHHs showed synergistic blocking. Multi-specific antibodies with enhanced affinity and avidity, and improved S/ACE2 blocking are currently being developed using an in-silico approach that also fuses VHHs to Fc domains. Importantly, our current bi-specific antibody shows potent S/ACE2 blocking (KD – 0.25 nM, IC100 ∼ 36.7 nM, IC95 ∼ 12.2 nM, IC50 ∼ 1 nM) which is significantly better than individual monoclonal VHH-Fcs. Overall, this design would equip the VHH-Fcs multiple mechanisms of actions against SARS-CoV-2. Thus, we aim to contribute to the battle against COVID-19 by developing therapeutic antibodies as well as diagnostics.